Growth Temperature Effects of Chemical Vapor Deposition‐Grown Boron Nitride Layer Using B2H6 and NH3. Issue 4 (20th November 2019) - Yamada, Hisashi; Inotsume, Sho; Kumagai, Naoto; Yamada, Toshikazu; Shimizu, Mitsuaki
Abstract : The boron nitride (BN) thin films on Al2 O3 substrates grown by chemical vapor deposition (CVD) using alternating supply of B2 H6 and NH3 are investigated. A significant reduction in growth rates is observed when the growth temperature ( T g ) is decreased from 1360 to 1140 °C, indicating incomplete decomposition of B2 H6 . The 2 θ / ω scans of high‐resolution X‐ray diffraction (HRXRD) reveal that the intensity ratio of 2 θ  = 26.7°/54.0° is 16, which is close to the theoretical intensity ratio for hexagonal BN ( h ‐BN) of 17. By reducing T g, the peak at 2 θ  = 26.2° is appeared, which is considered to the turbostratic BN ( t ‐BN). The Raman shift at 1369 cm −1 with a full width at half maximum of 20 cm −1 is analyzed, corresponding to the first‐order E 2g symmetry vibrational mode in h ‐BN. The high‐resolution transmission electron microscopy (HRTEM) confirms aligned 2D stacking of BN layers and the distance between interlayers of 0.3326 nm. The interlayers of 1.0 nm AlON are identified between BN layers and Al2 O3 substrate. Abstract : Growth temperature effects of chemical vapor deposition‐grown boron nitride (BN) layer using B2 H6 and NH3 have been investigated. A significant reduction in growth rates is observed when the T g is decreased from 1360 to 1140 °C, indicating incomplete decomposition of B2 H6 . The interlayers of 1.0 nm AlON are identified between BN layers and Al2 O3 substrate.